2016
DOI: 10.1080/09513590.2016.1183193
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism is associated with metabolic syndrome and clomiphene citrate resistance in women with polycystic ovary syndrome

Abstract: SCH was found associated with IR, MS and CC resistance in women with PCOS. PCOS patients with SCH may have a poorer treatment response to ovulation induction with CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…An analysis of results was possible in the case of total testosterone levels, which The LH/FSH ratio was reported by four studies. None of them reported significant differences (22,25,27,33). Finally, among the four studies that reported outcomes related to SHBG levels, only Dittrich reported that they were significantly reduced in the study group (33.65 ± 17.21 vs 43.55 ± 18.20 nmol/L, P = 0.01) (27,28,29,32).…”
Section: Hormonal Profilementioning
confidence: 96%
See 1 more Smart Citation
“…An analysis of results was possible in the case of total testosterone levels, which The LH/FSH ratio was reported by four studies. None of them reported significant differences (22,25,27,33). Finally, among the four studies that reported outcomes related to SHBG levels, only Dittrich reported that they were significantly reduced in the study group (33.65 ± 17.21 vs 43.55 ± 18.20 nmol/L, P = 0.01) (27,28,29,32).…”
Section: Hormonal Profilementioning
confidence: 96%
“…Twelve studies were finally included in the present review, which enrolled 2654 PCOS patients (22,23,24,25,26,27,28,29,30,31,32,33). Among them, 577 women had PCOS and SCH and the remaining 2077 had PCOS only.…”
Section: Included Studiesmentioning
confidence: 99%
“…Clinically-overt hypothyroidism is characterized by weight gain, cold intolerance, fluid retention, bradycardia, and hypercholesterolemia. Recent evidences demonstrate that subclinical hypothyroidism, defined as elevated thyroid-stimulating hormone (TSH) levels beyond normal range with normal thyroxine levels, is also associated with increased blood pressure, serum cholesterols [8,9,10,11], and cardiovascular disease risk [12,13,14]. In this study, we further explore whether TSH level within the normal limit is associated with cardiometabolic risk factors including central obesity, insulin resistance, high blood pressure, dyslipidemia, and inflammation in a large population-based study.…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al[13] 2014 China Rotterdam criteria 4.0 IU/l Patients who had hypertension, hypercholesterolemia, congenital adrenal hyperplasia, hypothyroidism or hyperthyroidism, Cushing's disease, hyperprolactinemia, and who used specific medications (e.g., oral contraceptives, corticosteroids, GnRH agonists and antagonists, insulin-sensitizing drugs, antiandrogens, aspirin) were excluded from the study within 3 months prior to enrollment Lu et al[14] 3.75 mIU/l Patients who had known history of diabetes mellitus, hyperprolactinemia, congenital adrenal hyperplasia, hypothyroidism or hyperthyroidism, Cushing's disease, renal, hepatic, or cardiac dysfunction, a history of ovarian or adrenal neoplasm, and those using any medication (e.g., oral contraceptives, insulin-sensitizing drugs, statins, radioactive iodine, levothyroxine, corticosteroids and GnRH agonists and antagonists) within 6 months of the enrolment to the study were excluded All subjects should be excluded: 1) previous diabetes, coronary heart disease, hyperlipidemia, hypertension, hypothalamus or pituitary diseases caused by diseases, malignant tumors, liver, kidney and other viscera substantive lesions, etc. ; 2) Past thyroid disease (whether cured or not), recent oral drugs affecting thyroid function and blood lipid levels, thyroid antibody positive in the past ▶table 1 Characteristics of included studies.Author(s) […”
mentioning
confidence: 99%